Polysomnographically mediated cognitive improvements in individuals with insomnia symptoms following continuous theta-burst stimulation of the default mode network - Huskey, Alisa; Fisher, Julia M.; Hildebrand, Lindsey; Negelspach, David; Henderson-Arredondo, Kymberly; Jankowski, Samantha; Patel, Salma I.; Chou, Ying-Hui; Dailey, Natalie S.; Killgore, William D. S. (Frontiers in Sleep, 2024)
Insomnia is associated with mild cognitive impairment, although the mechanisms of this impairment are not well understood. Neural characteristics of slow-wave and rapid eye movement sleep may help explain cognitive impairments common in insomnia. This investigation aimed to determine whether cognitive changes following continuous theta-burst stimulation (cTBS) are attributable to active stimulation, polysomnographic parameters of sleep, or both. Method: Data presented here are part of a larger pilot clinical trial aiming to treat insomnia by targeting a node in the default mode network using an inhibitory 40-second (cTBS). A double-blind counterbalanced sham-controlled crossover design was conducted. Participants (N=20) served as their own controls on two separate in-laboratory visitsone with active cTBS and the other with sham cTBS. Each visit included cognitive assessments before and after stimulation and following a night of sleep in the lab monitored with polysomnography. Results: Slow wave sleep duration influenced working memory in the active cTBS condition, with shorter duration predicting improvements in working memory post sleep (B = -0.003, p = 0.095). Onset latency to rapid eye movement sleep predicted subsequent working memory, regardless of treatment condition (B = -0.001, p = 0.040). Results suggest that changes in attention and processing speed were primarily due to slow wave sleep onset (B = -0.001, p = 0.017) and marginally predicted by slow wave sleep duration (B = 0.002, p = 0.081) and sleep efficiency (B = 0.006, p = 0.090). Conclusions: Findings emphasize the important role that timing of slowwave and rapid eye movement sleep have on information processing. Future work using larger sample sizes and more stimulation sessions is needed to determine optimal interactions between timing and duration of slow wave and rapid eye movement throughout the sleep period.